3D-FVM anisotropic model for eddy current problems related to composite materials. Issue 4 (2nd October 2018) - Lakhdari, A.; Cheriet, A.; Feliachi, M.
ABSTRACT: In this paper, a 3D-finite volume method model is developed to analyse eddy current problems related to anisotropic conductive materials. Two unidirectional composite materials (boron fibres reinforced aluminium alloy, carbon fibres reinforced polymer) are studied. To be adapted to such problem, the finite volume implementation of the A – V formulation has been carried out by using the unstructured mesh, where the prism shape of the elementary volume is introduced. The effects of the mesh type either prism mesh or hexahedral mesh on the accuracy and the CPU time are carefully analysed. The anisotropy ratio on the eddy current distribution is also discussed. The developed numerical model is validated by comparison to experimental results.